2007
DOI: 10.1007/s00424-007-0215-5
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen treatment of myocardial infarcted female rats exacerbates scar formation

Abstract: Hormonal replacement therapy in postmenopausal women was associated with an increased incidence of nonfatal myocardial infarction. Selective estrogen receptor modulators were considered an alternative pharmacological approach. However, selective estrogen receptor modulators acting via estrogen receptor-dependent and receptor-independent mechanisms may negatively influence cardiac remodeling. The present study tested the hypothesis that tamoxifen (TAM) treatment after coronary artery ligation compromised scar f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…The cardiac fibroblast populations can also be distinguished by nestin expression, as the intermediate filament protein was highly expressed in neonatal rat ventricular fibroblasts, significantly downregulated in adult ventricular fibroblasts and re‐induced in a subpopulation of scar myofibroblasts [Beguin et al, 2012]. The present study has further demonstrated that scar myofibroblasts plated alone on matrigel in the absence of an angiogenic peptide were capable of self assembly and formation of lumen‐like structures akin to that reported by endothelial cells [Geraldes et al, 2007]. By contrast, neither neonatal nor adult ventricular fibroblasts were capable of recapitulating an endothelial cell‐like response when plated on matrigel.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The cardiac fibroblast populations can also be distinguished by nestin expression, as the intermediate filament protein was highly expressed in neonatal rat ventricular fibroblasts, significantly downregulated in adult ventricular fibroblasts and re‐induced in a subpopulation of scar myofibroblasts [Beguin et al, 2012]. The present study has further demonstrated that scar myofibroblasts plated alone on matrigel in the absence of an angiogenic peptide were capable of self assembly and formation of lumen‐like structures akin to that reported by endothelial cells [Geraldes et al, 2007]. By contrast, neither neonatal nor adult ventricular fibroblasts were capable of recapitulating an endothelial cell‐like response when plated on matrigel.…”
Section: Discussionsupporting
confidence: 62%
“…Myocardial infarction (MI) was induced in male Sprague–Dawley rats (9–11 weeks old; Charles Rivers, St. Constant, Canada) following ligation of the left anterior descending coronary artery as previously described [Geraldes et al, 2007]. Scar myofibroblasts were isolated from the infarct region of 1‐week post‐MI male rats and adult cardiac fibroblasts isolated from the left ventricle of normal male Sprague–Dawley rats (9–11 weeks old; Charles Rivers), as previously described [Calderone et al, 2006; Beguin et al, 2012].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8] The smaller infarct was not attributed to the presence of estrogen and progesterone as ovariectomized adult female rodents subjected to complete coronary artery ligation did not translate to scar expansion. [9][10][11][12] Moreover, experimental studies performed in rodents reported that recruitment of cardiac sarcolemma K ATP channels provided sex-specific cardioprotection to the female adult rodent heart in response to ischemic injury. 4,5 The cardiac K ATP channel is composed of the pore-forming subunit Kir6.2 and the auxiliary sulfonylurea receptor subunit SUR2A and channel activity rapidly adjusted membrane excitability in response to changes in the energetic status of the cell.…”
Section: Introductionmentioning
confidence: 99%
“…The latter paradigm extended to rodents as a smaller infarct size was identified in females compared to males in experimental models of ischemic injury 4–8 . The smaller infarct was not attributed to the presence of estrogen and progesterone as ovariectomized adult female rodents subjected to complete coronary artery ligation did not translate to scar expansion 9–12 . Moreover, experimental studies performed in rodents reported that recruitment of cardiac sarcolemma K ATP channels provided sex‐specific cardioprotection to the female adult rodent heart in response to ischemic injury 4,5 .…”
Section: Introductionmentioning
confidence: 99%